ENTERPRISE ARCHITECTURE PLANNING SISTEM INFORMASI PELAYANAN PUBLIK MENGGUNAKAN ZACHMAN FRAMEWORK DI PEMERINTAH KOTA YOGYAKART - , Joko Marwiyanto ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Public services have a very important position in the government. W ithout good public services, the level of people's satisfaction on the course of government will be impacted. Improved public services require the support of information technology . The first step in the development of an integrated information system is to establish the strategic planning of information systems supporting the business needs. Spewak (1992) developed a method of Enterprise Architecture Planning (EAP) for information systems development planning. EAP was developed based on the Zachman Framework, which is widely used due to systematic, easy to understand and usefullness as a control for the future information systems development. The result of this study is the blueprint design of Enterprise Architecture Planning (EAP) of Public Service Information System in Pemerintah Kota Yogyakarta which includes data, applications and technology which are defined as 32 business processes. Data architecture generated 44 data entities and relationships. Application architecture obtained 15 proposed applications, while the technology architecture generated the architecture of enterprise networks concept.